3y = 2x + 6
x + y = 7
y = 7 - x
3(7 - x) = 2x + 6
21 - 3x = 2x + 6
21 - 6 = 2x + 3x
15 = 5x
15/5 = x
3 = x
x + y = 7
3 + y = 7
y = 7 - 3
y = 4
Solution is (3,4)
Answer:
x + 8
Step-by-step explanation:
x + 5 + 3.
add the numbers
↓
x + 8
Answer:
99.7%
Step-by-step explanation:
Given that mean (μ) = 394.3 ms and standard deviation (σ) = 84.6 ms.
The empirical rule states that for a normal distribution:
- 68% falls within one standard deviation (μ ± σ)
- 95% falls within two standard deviation (μ ± 2σ)
- 99.7% falls within three standard deviation (μ ± 3σ)
one standard deviation = 394.3 ± 84.6 = (309.7, 478.9). 68% falls within 309.7 and 478.9 ms
two standard deviation = 394.3 ± 2 × 84.6 = (225.1, 563.5). 95% falls within 225.1 and 563.5 ms
three standard deviation = 394.3 ± 3 × 84.6 = (140.5, 648.1). 99.7% falls within 140.5 and 648.1 ms
Answer:
-2(6x-13)/15
Step-by-step explanation:
This is done by simplifying the expression as well as combining like terms
yikes i remember doing this but.... i completely forgot ;–; i really wish i could help